If it's not what You are looking for type in the equation solver your own equation and let us solve it.
57+3=11x-5x
We move all terms to the left:
57+3-(11x-5x)=0
We add all the numbers together, and all the variables
-(+6x)+57+3=0
We add all the numbers together, and all the variables
-(+6x)+60=0
We get rid of parentheses
-6x+60=0
We move all terms containing x to the left, all other terms to the right
-6x=-60
x=-60/-6
x=+10
| -16+x=-8-5x | | 6x2=3x+1 | | 2(x+4)=4+8x | | 653268456•7946397654973976397469746977643t=75427543754275437475247534 | | 2(2x+3)=2(x-4) | | 65x+4=150 | | 1=-7-7x-x | | 2x+5+3x-1=2x+19 | | −2m+8=12 | | 3-2x=10x-7x+1 | | 8/2=2/r | | 5+3(x-8)=11 | | 5/3x+1/3x-+7+1/3=0 | | 2(77-2y)+4y=154 | | -x-12x-12+3=-48 | | 5y+25=-10y+40 | | 8y+32=-17-y | | -2X2+5x+12=0 | | -2/1=5-c/4 | | -34=15x+18+11x | | 23w2+9w=0 | | 980x^2-20x-800=0 | | 9n+7n-2=50 | | 5/3x+1/3x=71/3=8/3x | | 63+83+7c+27=180 | | 4.9t^2+20t+12=0 | | 28=f−30 | | -4(x+3)=-2x+2 | | 3x+26x+4=x-2/3 | | 19h-9h=10 | | -3x+14=-1+7 | | 3w+3+98+w+27=180 |